TRANSPORTATION OF CARGO BY HEAVY HAUL TRUCKS - Приходько, Всеволод; Вікович, Ігор (Modern engineering and innovative technologies, 2024)
The transportation of various cargoes by the most modern heavy haul trucks has been considered. The advantages of transporting heavy cargoes by multi-link trucks over freight vehicles have been substantiated. Diagrams of the traction-coupling devices of